Informe sobre la Formación inicial y continua de Profesores de Matemáticas: El caso de Colombia - Guacaneme, Edgar Alberto (2013)
This document offers an overview of certain aspects about the structure, development, precedent and limitations of the initial and continued training of mathematics teachers in Colombia. In particular, we mention some aspects about the transformations that the training of mathematics teachers has suffered as a product of political, social and academic policies. Additionally we describe the current training guidelines at the pre- and post-graduate level. Finally we comment on how some of the networks and organizations in mathematical education articulate with instances related to the training of teachers in the field of mathematics. Similarly, we discuss about the need for future developments in the training of mathematics teachers which should result in collective efforts aimed towards the creation of a national training system of mathematics teachers.